Análise da presença e articulação teórica da Catalogação de Assunto na literatura científica da International Society for Knowledge Organization ISKO: uma análise de domínio - Ferreira, Gustavo Meletti [UNESP]; Guimarães, José Augusto Chaves [UNESP] (My University, 2011)
Subject Cataloging is one of the processes of subject approach to information, beside indexing and subject analysis. In this sense, this research is a part of a broader project which analyses ISKO as an academic space that promotes a dialogical dimension among those theoretical questions. In this sense, it aims to analyze the presence of subject cataloguing in the discussions of knowledge organization as well as how the authors of such subject dialogue each other. Considering the questions, the full collection of ISKO and ISKO-Spain conference proceedings were analyzed in order to verify how present were subject cataloguing matters in those collections. It was possible to identify a group of 36 articles (27 from International ISKO and 9 from ISKO – Spain) whose references were bibliometrically analyzed in terms of documentary forms, average life, language and citation analysis. The results showed that the major ISKO and ISKO-Spain literature on subject cataloguing is based on journal articles, mostly published in English, presenting a relatively young average life (14 years for ISKO and 10 for ISKO-Spain).

Considerando o importante papel desempenhado pela Catalogação de Assunto no universo teórico-metodológico do tratamento temático da informação, buscou-se analisar a construção de seu referencial teórico na ISKO. Para tanto, partiu-se de um estudo históricoconceitual para se chegar à análise das 36 comunicações (27 na ISKO e 9 na ISKO – Espanha) referentes a esse tema. A esse corpus procedeu-se uma análise bibliométrica relativa às fontes documentais utilizadas (forma, língua e vida média) e aos autores citados (redes de citação por meio do software PAJEK). Os resultados da análise revelaram uma presença ainda tímida dessa temática no universo analisado, destacando-se a predominância de fontes documentais baseadas em artigos de periódicos, publicados em inglês, com vida média jovem (14 anos para ISKO e 11 para ISKO-Espanha).